An electrolyte restoring agent
By adding H2O2 as a green reducing agent to the positive electrode electrolyte of an alkaline iron-based liquid flow battery, Fe(CN)63-to Fe(CN)64-, the problem of battery capacity and efficiency attenuation is solved, and the battery is realized The multiple recovery and stable operation of the electrolyte significantly reduces maintenance costs.
Patent Information
- Application Number
- CN202111066710.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-09-10
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2041-09-10
AI Technical Summary
During the charging and discharging process of alkaline iron-based liquid flow batteries, especially during the charging and discharging process of the first round of the battery, the electrolyte needs to be activated, resulting in low efficiency of the battery; at the same time, the negative electrode oxidation and reduction pairs undergo side reactions, resulting in positive electrode activity. The substance Fe(CN) 63-accumulates, resulting in attenuation of battery capacity and efficiency.
The accumulated Fe(CN) 63- is reduced to Fe(CN) 64- by adding green reducing agent H2O2 or H2O2 to the positive electrode electrolyte after the battery/pile runs at least one cycle, thereby restoring the battery. /Pile capacity and efficiency.
The battery/pile capacity and efficiency recovery is achieved, and the impurity elements are not introduced into the electrolyte are allowed to be restored multiple times. The process is simple, the operation is easy, and the raw materials are easy to obtain, which significantly reduces maintenance costs.
Smart Images

Figure CN115799585B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of liquid flow batteries, and specifically relates to a positive electrode electrolyte with a redox couple of Fe(CN) 6 3- / Fe(CN) 6 4- A recovery method for cathode electrolyte of alkaline iron-based flow battery. Background Art
[0002] Fe(CN) 6 3- / Fe(CN) 6 4- Alkaline iron-based flow batteries, as positive electrode redox couples, have the advantages of low electrolyte cost and excellent redox couple kinetics. They have good application prospects in the field of energy storage, especially in distributed energy storage, grid peak regulation, wind power, solar power and other renewable energy generation.
[0003] Fe(CN) 6 3- / Fe(CN) 6 4- During the charging and discharging process of the alkaline iron-based flow battery as the positive electrode redox couple, especially during the first cycle of the battery charging and discharging, the electrolyte needs to be activated, resulting in a low coulombic efficiency of the battery; in addition, during the operation of the battery, the negative electrode redox couple undergoes side reactions (for example, for alkaline zinc-iron flow batteries and alkaline zinc-iron-nickel hybrid flow batteries, the metal zinc deposited on the electrode by the negative electrode zincate has a loose porous structure, has a weak bonding force with the electrode, and is easy to fall off the electrode; on the other hand, metal zinc is easily corroded by alkali in an alkaline environment, which reduces the amount of negative electrode active material, and the positive electrode active material matched with the negative electrode cannot be fully utilized during the discharge process, resulting in the positive electrode active material -Fe(CN) 6 3- Accumulation. As the charge and discharge cycles proceed, Fe(CN) accumulated at the positive electrode 6 3- The concentration gradually increases, causing the battery to charge during the Fe(CN) 6 4- The concentration of Fe(CN) gradually decreases. 6 4- This causes the concentration polarization of the battery to increase during the charging process, resulting in a decrease in battery capacity and efficiency, which restricts the practical application of alkaline iron-based flow batteries.
[0004] Patent CN111261889A discloses a method for online recovery of positive electrode electrolyte of alkaline zinc-iron liquid flow battery. The patent uses positive electrode electrolyte of alkaline zinc-iron liquid flow battery whose positive electrode capacity is reduced to more than 85% of theoretical capacity as raw material, adds inorganic and organic reducing agents such as hydroxylamine hydrochloride, hydroxylamine sulfate, ascorbic acid, etc., to recover Fe(CN) accumulated in the positive electrode of the battery. 6 3- Reduction to Fe(CN) 6 4- , to restore the battery capacity and battery efficiency. However, the reducing agent added in the patent will introduce Cl into the initial electrolyte. - 、SO 4 2- As the number of electrolyte recovery increases, the content of impurity elements introduced into the positive electrolyte increases. Under the influence of the common ion effect, the positive active material Na 4 Fe(CN) 6 or K 4 Fe(CN) 6 The precipitation is not conducive to the multiple recovery of the battery electrolyte. Summary of the invention
[0005] In view of the above problems, the present invention provides a Fe(CN) 6 3- / Fe(CN) 6 4- A green recovery method for the positive electrode electrolyte of alkaline iron-based liquid flow batteries as a positive electrode redox couple can repeatedly solve the accumulation of Fe(CN) in the positive electrode electrolyte during the operation of the battery / stack 6 3- The problem of capacity and efficiency attenuation caused by this can be solved, and the battery electrolyte can be reused.
[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0007] A positive electrode electrolyte redox couple is Fe(CN) 6 3- / Fe(CN) 6 4- The invention discloses a method for recovering the cathode electrolyte of an alkaline iron-based liquid flow battery, wherein the cathode electrolyte after the battery / stack has been operated for at least one cycle is taken as the recovery object, and the Fe(CN) accumulated in the cathode electrolyte is reduced by adding a green reducing agent. 6 3- Reduction, so that the Fe(CN) accumulated in the positive electrode electrolyte 6 3- Reduction to Fe(CN) 6 4- , thereby restoring the capacity and efficiency of the battery / stack. The principle is as follows:
[0008]
[0009] The green reducing agent is H 2 O 2 or H 2 O 2 Mixed with alkaline solution; initial positive electrode electrolyte is 0.2-1M Fe(CN) 6 3- and 0-3M NaOH or KOH alkaline solution. The purpose of adding alkaline solution is to convert H 2 O 2 The protons in the electrolyte are neutralized, making the added green reducing agent nearly neutral without consuming the OH- in the electrolyte.
[0010] Based on the above scheme, preferably, the alkaline solution is one or a mixed solution of more than one of NaOH solution, KOH solution and LiOH solution.
[0011] Based on the above scheme, preferably, the green reducing agent added contains H 2 O 2 The amount of Fe(CN) in the positive electrode electrolyte at the end of battery / stack discharge 6 3- The concentration of H 2 O 2 The amount of Fe(CN) in the positive electrode electrolyte at the end of battery / stack discharge 6 3- The molar concentration ratio is 1:4-2:1; preferably 1:1.
[0012] Based on the above scheme, preferably, Fe(CN) in the positive electrode electrolyte 6 3- The concentration was measured by UV-visible spectrophotometer.
[0013] Based on the above scheme, preferably, the green reducing agent is added after the battery / fuel stack has been running for a period of time. During the process of adding the green reducing agent, the positive electrode electrolyte may circulate through the battery / fuel stack or not.
[0014] Based on the above scheme, preferably, the cathode electrolyte can be restored multiple times by adding a green reducing agent.
[0015] Based on the above scheme, preferably, the reduction reaction time is 1 minute to 5 hours.
[0016] Based on the above scheme, preferably, the positive electrode electrolyte recovery method can be used in alkaline iron-based liquid flow battery cells, battery stacks and systems.
[0017] Based on the above scheme, preferably, the alkaline iron-based liquid flow battery includes an alkaline zinc-iron liquid flow battery, an alkaline zinc-iron-nickel hybrid liquid flow battery, an alkaline all-iron liquid flow battery, an alkaline quinone-iron liquid flow battery, and the like.
[0018] Beneficial results of the present invention:
[0019] 1. The present invention is carried out by using Fe(CN) 6 3- / Fe(CN) 6 4- Adding green reductant to the positive electrolyte of alkaline iron-based flow battery as positive electrode redox couple can solve the problem of Fe(CN) accumulation in the positive electrolyte during battery / stack operation. 6 3- The problem of capacity and efficiency attenuation caused by this will not introduce impurity elements into the electrolyte and can be restored multiple times. The chemical reduction method is used at room temperature and pressure, with simple process, easy operation and readily available raw materials, which can significantly restore the battery capacity and efficiency.
[0020] 2. The present invention uses a small amount of chemical reagents, and the byproducts are water and oxygen, which is non-polluting to the environment.
[0021] 3. The present invention has low power consumption, saves energy, and the properties of the electrolyte after recovery are stable.
[0022] 4. The green reducing agent used in the present invention will not have a significant impact on cost control.
[0023] 5. The present invention solves the problem of battery capacity / efficiency recovery after the battery capacity / efficiency decreases by adding a green reducing agent to the positive electrode electrolyte of the alkaline iron-based liquid flow battery, thereby greatly reducing the maintenance cost of the alkaline iron-based liquid flow battery, the battery stack and the system. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 (a) 1 mM Fe(CN) 6 3- + UV spectrum of 3M NaOH solution; (b) 1mM Fe(CN) 6 3- +3M NaOH +1.5mM H 2 O 2 UV spectrum of the solution.
[0025] Figure 2 With 0.6M Fe(CN) 6 3- +3M NaOH as the positive electrolyte of alkaline zinc-iron flow battery at 80mA cm -2 Charge and discharge curves under working current density conditions (Comparative Example 2).
[0026] Figure 3 With 0.6M Fe(CN) 6 3- +3M NaOH+0.65MH 2 O 2 Alkaline zinc-iron flow battery with positive electrolyte at 80 mA cm -2 The charge and discharge curves and performance diagrams under working current density conditions (Example 2), wherein the left figure is a charge and discharge curve diagram; the right figure is a diagram of battery efficiency versus cycle number.
[0027] Figure 4 At the end of the 73rd cycle of the kW-class alkaline zinc-iron flow battery stack, the cathode electrolyte was diluted 400 times and H 2 O 2 UV spectra of the electrolyte before and after, where the left picture corresponds to Example 3 and the right picture corresponds to Example 3.
[0028] Figure 5 Adding H to the positive electrolyte of the kW-class alkaline zinc-iron flow battery stack 2 O 2 The charge-discharge curves before and after (71th to 76th), where the first three cycles (i.e. the end of charging, the part where the charging voltage rises suddenly) are the ones where H is added 2 O 2 The first and last three cycles (i.e. the end of charging, when the charging voltage does not exceed 21V) are the time for adding H 2 O 2 back. DETAILED DESCRIPTION
[0029] The following is further described in conjunction with specific examples so that the advantages and features of the present invention can be more easily understood by those skilled in the art. The raw materials used in the following examples are all commercially available conventional products.
[0030] Comparative Example 1
[0031] Prepare 1mM Fe(CN) 6 3- +3mol L -1 The NaOH solution was subjected to UV-visible spectroscopy analysis. Figure 1 a It can be seen that Fe(CN) 6 3- There is a characteristic absorption peak at 421nm.
[0032] Example 1
[0033] To confirm H 2 O 2 Can reduce Fe(CN) 6 3- , prepared with 1mM Fe(CN)6 3- +3M NaOH +1.5mM H 2 O 2 The solution was analyzed by UV-visible spectroscopy. Figure 1 b It can be seen that adding H 2 O 2 After that, Fe(CN) 6 3- The characteristic absorption peak at 421 nm wavelength disappears, indicating that Fe(CN) in the solution 6 3- Can be H 2 O 2 reduction.
[0034] Comparative Example 2
[0035] Assemble an alkaline zinc-iron flow battery cell and test its battery performance. The cathode electrolyte composition is 60mL 0.6M Fe(CN) 6 3- +3M NaOH; the negative electrode electrolyte composition is 60mL 0.3mol L -1 Zn(OH) 4 2- +3mol L - 1 NaOH; at 80 mA cm -2 The current density was 80 mA cm-1 for 10 min and then the voltage was cut off. -2 The current density is 0.1V. 6 3- / Fe(CN) 6 4- The electrochemical reaction of the positive electrode of the alkaline iron-based flow battery as the positive electrode redox couple is as follows:
[0036]
[0037] When the battery is charging, the positive electrode Fe(CN) 6 4- Lose electrons and oxidize to Fe(CN) 6 3- The discharge process is the opposite; when the active substances in the initial electrolyte are all Fe(CN) 6 3- The battery cannot be charged ( Figure 2 ).
[0038] Example 2
[0039] To further confirm that H 2 O 2Can reduce Fe(CN) 6 3- , assembled an alkaline zinc-iron flow battery cell and tested its battery performance. The cathode electrolyte composition was 60mL 0.6M Fe(CN) 6 3- +3M NaOH+0.65MH 2 O 2 (0.6M Fe(CN) 6 3- +3M NaOH solution is prepared and then add 0.65MH 2 O 2 , in order to convert Fe(CN) 6 3- Reduction to Fe(CN) 6 4- ); the negative electrode electrolyte composition is 60mL 0.3mol L -1 Zn(OH) 4 2- +3mol L -1 NaOH; at 80 mA cm -2 The current density was 80 mA cm-1 for 10 min and then the voltage was cut off. -2 The positive electrode electrolyte in this embodiment is 60mL 0.6M Fe(CN) 6 3- +3M NaOH+0.65MH 2 O 2 , where H 2 O 2 Fe(CN) 6 3- Reduction to Fe(CN) 6 4- , so that the battery can be charged and discharged normally ( Figure 3 ) and maintain high battery performance, further confirming that H 2 O 2 It can be used as a green reducing agent to convert Fe(CN) 6 3- Reduction to Fe(CN) 6 4- .
[0040] Comparative Example 3
[0041] Assemble kW-class alkaline zinc-iron flow battery stack and test the stack performance. The cathode electrolyte composition is 30L 0.8mol L -1 Fe(CN) 6 4- +3mol L-1 KOH; the negative electrode electrolyte composition is 30L 0.6mol L -1 Zn(OH) 4 2- +4mol L - 1 NaOH; at 40 mA cm -2 The current density was 40 mA cm-1 and the charge was carried out for 70 min. Then the voltage was cut off and the charge was carried out for 70 min. -2 The battery was discharged to 8V under the current density of 2.5V. At the end of the 73rd cycle discharge, the UV spectrum of the positive electrode electrolyte diluted 400 times is as follows: Figure 4 As shown in the left figure, it can be seen that there is Fe(CN) at 421nm 6 3- Characteristic absorption peak, calculated to obtain the accumulated Fe(CN) in the positive electrode electrolyte 6 3- The concentration is 0.1844 mol L -1 ; Due to the Fe(CN) in the positive electrolyte 6 3- The accumulation of Fe(CN) in the battery stack during the next cycle charging process 6 4- As the concentration decreases, the concentration polarization of the stack becomes larger at the end of charging, and the stack voltage increases significantly at the end of charging ( Figure 5 ).
[0042] Example 3
[0043] Add H to the positive electrolyte at the end of the 73rd cycle discharge. 2 O 2 The content is 6 mol H 2 O 2 After 1 hour of reaction, the positive electrolyte was taken and the UV spectrum after dilution 400 times was as follows Figure 4 As shown in the figure on the right, it can be seen that Fe(CN) at 421nm 6 3- The characteristic absorption peak basically disappears, and the accumulated Fe(CN) in the positive electrode electrolyte is calculated. 6 3- The concentration decreased to 0.05662 mol L -1 ; Continuing to charge the stack, it was found that the concentration polarization phenomenon disappeared significantly at the end of stack charging ( Figure 5 ), further confirming that H 2 O 2 It can be used as a green reducing agent to convert Fe(CN) 6 3- Reduction to Fe(CN) 6 4-, thereby improving the operational stability of the fuel cell stack.
[0044] Comparative Example 4
[0045] Assemble alkaline zinc-iron flow battery cells and test the battery performance. The cathode electrolyte composition is 60mL 0.8mol L -1 Fe(CN) 6 4- +3mol L -1 KOH; the negative electrode electrolyte composition is 60mL 0.6mol L -1 Zn(OH) 4 2- +4mol L - 1 NaOH; at 80 mA cm -2 The current density was 80 mA cm-1 for 15 min and then the voltage was cut off. -2 The battery was discharged to 0.1 V under the current density of . The accumulated Fe(CN) in the electrolyte at the end of the 104th cycle discharge was measured by UV spectrophotometer. 6 3- The concentration is 0.1015 mol L -1 ; Due to the Fe(CN) in the positive electrolyte 6 3- The accumulation of Fe(CN) in the battery during the next cycle charging process 6 4- As the concentration decreases, the concentration polarization becomes larger at the end of charging, and the voltage tends to increase.
[0046] Example 4
[0047] Add H to the positive electrolyte at the end of the 104th cycle discharge. 2 O 2 The content is 0.01 mol H 2 O 2 After the reaction for 0.5 hours, the positive electrolyte was taken and the accumulated Fe(CN) in the positive electrolyte was measured by UV spectrophotometer. 6 3- The concentration was reduced to 0.01013 mol L -1 ; The battery continued to be charged and it was found that the concentration polarization phenomenon at the end of battery charging disappeared significantly, and the battery ran stably for more than 400 cycles and its performance remained stable.
[0048] Comparative Example 5
[0049] Assemble alkaline zinc-iron flow battery cells and test the battery performance. The cathode electrolyte composition is 60mL 0.8mol L -1 Fe(CN)6 4- +3mol L -1 KOH; the negative electrode electrolyte composition is 60mL 0.6mol L -1 Zn(OH) 4 2- +4mol L - 1 NaOH; at 80 mA cm -2 The current density was 80 mA cm-1 for 15 min and then the voltage was cut off. -2 The battery was discharged to 0.1 V under the current density of . The accumulated Fe(CN) in the electrolyte at the end of the 118th cycle discharge was measured by UV spectrophotometer. 6 3- The concentration is 0.1124 mol L -1 ; Due to the Fe(CN) in the positive electrolyte 6 3- The accumulation of Fe(CN) in the battery during the next cycle charging process 6 4- As the concentration decreases, the concentration polarization becomes larger at the end of charging, and the voltage gradually increases.
[0050] Example 5
[0051] Add 5 mL of 1.2 mol L -1 H 2 O 2 +1mol L -1 After 2 hours of reaction, the positive electrolyte was taken and the accumulated Fe(CN) in the positive electrolyte was measured by UV spectrophotometer. 6 3- The concentration decreased to 0.009171 mol L -1 ; The battery continued to be charged and it was found that the concentration polarization phenomenon at the end of battery charging disappeared significantly, and the battery ran stably for more than 300 cycles and its performance remained stable.
[0052] Comparative Example 6
[0053] Assemble alkaline zinc-iron flow battery cells and test the battery performance. The cathode electrolyte composition is 60mL 0.8mol L -1 Fe(CN) 6 4- +3mol L -1 KOH; the negative electrode electrolyte composition is 60mL 0.6mol L -1 Zn(OH) 4 2- +4mol L -1 NaOH; at 80 mA cm -2 The current density was 80 mA cm-1 for 15 min and then the voltage was cut off. -2 The battery was discharged to 0.1 V under the current density of . The accumulated Fe(CN) in the electrolyte at the end of the 142nd cycle discharge was measured by UV spectrophotometer. 6 3- The concentration is 0.1218 mol L -1 ; Due to the Fe(CN) in the positive electrolyte 6 3- The accumulation of Fe(CN) in the battery during the next cycle charging process 6 4- As the concentration decreases, the concentration polarization becomes larger at the end of charging, and the voltage increases significantly.
[0054] Example 6
[0055] Add 6 mL of 1.2 mol L -1 H 2 O 2 +0.5mol L -1 NaOH + 0.5 mol L -1 After 2 hours of reaction with KOH solution, the positive electrolyte was taken and the accumulated Fe(CN) in the positive electrolyte was measured by UV spectrophotometer. 6 3- The concentration decreased to 0.008967 mol L -1 ; The battery continued to be charged and it was found that the concentration polarization phenomenon at the end of battery charging disappeared significantly, and the battery ran stably for more than 350 cycles and its performance remained stable.
[0056] Comparative Example 7
[0057] Assemble alkaline zinc-iron flow battery cells and test the battery performance. The cathode electrolyte composition is 60mL 0.8mol L -1 Fe(CN) 6 4- +3mol L -1 KOH; the negative electrode electrolyte composition is 60mL 0.6mol L -1 Zn(OH) 4 2- +4mol L - 1 NaOH; at 80 mA cm -2 The current density was 80 mA cm-1 for 15 min and then the voltage was cut off. -2The battery was discharged to 0.1 V under the current density of . The accumulated Fe(CN) in the electrolyte at the end of the 102nd cycle discharge was measured by UV spectrophotometer. 6 3- The concentration is 0.1011 mol L -1 ; Add 6mL 1.0mol L -1 Hydroxylamine sulfate NaOH solution (NaOH concentration is 1 mol L -1 , the same below), after the reaction, the positive electrode electrolyte was taken, and the accumulated Fe(CN) in the positive electrode electrolyte was measured by ultraviolet spectrophotometer 6 3- The concentration was reduced to 0.009115 mol L -1 ; The battery was charged continuously and found that the concentration polarization phenomenon disappeared significantly at the end of the battery charging. After the battery ran for 218 cycles, the accumulated Fe(CN) in the electrolyte was measured by UV spectrophotometer at the end of the 218th cycle discharge. 6 3- The concentration is 0.1178 mol L -1 ; Continue to add NaOH solution containing 0.005 mol of hydroxylamine sulfate to the above positive electrode electrolyte, take the positive electrode electrolyte after the reaction, and measure the accumulated Fe(CN) in the positive electrode electrolyte by ultraviolet spectrophotometer 6 3- The concentration was reduced to 0.01018 mol L -1 Continuing to charge the battery, it was found that the concentration polarization phenomenon disappeared significantly at the end of the battery charging. After the battery ran for 422 cycles, the UV spectrophotometer was used to measure the accumulated Fe(CN) in the electrolyte at the end of the 422nd cycle discharge. 6 3- The concentration is 0.1826 mol L -1 ; Continue to add NaOH solution containing 0.01 mol of hydroxylamine sulfate to the above positive electrode electrolyte, take the positive electrode electrolyte after the reaction, and measure the accumulated Fe(CN) in the positive electrode electrolyte by ultraviolet spectrophotometer 6 3- The concentration decreased to 0.009117 mol L -1 The battery was charged continuously and the concentration polarization phenomenon disappeared obviously at the end of the battery charging. After the battery was operated for 446 cycles, due to the introduction of more 5O 4 2- Under the influence of the common ion effect, sodium ferrocyanide / potassium ferrocyanide solids precipitate in the positive electrode electrolyte storage tank, the battery cannot continue to be charged to the set capacity, and the battery capacity and efficiency are significantly reduced.
[0058] Example 7
[0059] Assemble alkaline zinc-iron flow battery cells and test the battery performance. The cathode electrolyte composition is 60mL 0.8mol L -1 Fe(CN) 6 4- +3mol L -1 KOH; the negative electrode electrolyte composition is 60mL 0.6mol L -1 Zn(OH) 4 2- +4mol L - 1 NaOH; at 80 mA cm -2 The current density was 80 mA cm-1 for 15 min and then the voltage was cut off. -2 The battery was discharged to 0.1 V under the current density of . The accumulated Fe(CN) in the electrolyte at the end of the 114th cycle discharge was measured by UV spectrophotometer. 6 3- The concentration is 0.1035 mol L -1 ; Add 5.5mL 1.2mol L to the above positive electrolyte -1 H 2 O 2 +1molL -1 After the reaction, the positive electrolyte was taken and the accumulated Fe(CN) in the positive electrolyte was measured by UV spectrophotometer. 6 3- The concentration decreased to 0.008779 mol L -1 ; The battery was charged continuously and found that the concentration polarization phenomenon disappeared significantly at the end of the battery charging. After the battery ran for 224 cycles, the accumulated Fe(CN) in the electrolyte was measured by UV spectrophotometer at the end of the 224th cycle discharge. 6 3- The concentration is 0.1214 mol L -1 ; Continue to add 0.01 mol H 2 O 2 After the reaction, the positive electrolyte was taken and the accumulated Fe(CN) in the positive electrolyte was measured by UV spectrophotometer. 6 3- The concentration was reduced to 0.01007 mol L -1 Continuing to charge the battery, it was found that the concentration polarization phenomenon disappeared significantly at the end of the battery charging. After the battery ran for 418 cycles, the UV spectrophotometer was used to measure the accumulated Fe(CN) in the electrolyte at the end of the 418th cycle discharge. 6 3- The concentration is 0.1779 mol L-1 ; Continue to add 0.015 mol H 2 O 2 After the reaction, the positive electrolyte was taken and the accumulated Fe(CN) in the positive electrolyte was measured by UV spectrophotometer. 6 3- The concentration decreased to 0.009022 mol L -1 Continuing to charge the battery, it was found that the concentration polarization phenomenon disappeared significantly at the end of the battery charging. After the battery ran for 592 cycles, the UV spectrophotometer was used to measure the accumulated Fe(CN) in the electrolyte at the end of the 592nd cycle discharge. 6 3- The concentration is 0.1565 mol L -1 ; Continue to add 0.01 mol H 2 O 2 After the reaction, the positive electrolyte was taken and the accumulated Fe(CN) in the positive electrolyte was measured by UV spectrophotometer. 6 3- The concentration decreased to 0.008779 mol L -1 , and continued to charge the battery. It was found that the concentration polarization phenomenon at the end of battery charging disappeared significantly, and the performance of the battery remained stable after 728 cycles. This shows that compared with the reducing agent disclosed in patent CN111261889A, the green reducing agent added in this patent will not introduce impurity elements into the electrolyte, and can be restored multiple times without affecting the stability of the positive electrode electrolyte.
[0060] The results of the embodiment show that the present invention adds a green reducing agent to the positive electrode electrolyte to make the Fe(CN) accumulated in the electrolyte 6 3- Reduction to Fe(CN) 6 4- , thereby achieving the purpose of restoring battery capacity and efficiency.
Claims
1. A method for recovering a cathode electrolyte of an alkaline iron-based flow battery, wherein the cathode electrolyte redox couple is Fe(CN)6 3- / Fe(CN)6 4- , characterized in that: The cathode electrolyte after the battery / stack has been running for at least one cycle is taken as the recovery object, and the accumulated Fe(CN)6 3- Reduction to Fe(CN)6 4- , thereby restoring the capacity and efficiency of the battery / stack, the green reductant is H2O2 or a mixture of H2O2 and an alkaline solution; the initial positive electrode electrolyte is 0.2-1M Fe(CN)6 3- and 0-3M NaOH or KOH alkaline solution.
2. The method for recovering the positive electrolyte of the alkaline iron-based liquid flow battery according to claim 1, characterized in that: The amount of H2O2 added to the green reducing agent is determined by the amount of Fe(CN)6 in the positive electrode electrolyte at the end of the battery / stack discharge. 3- The concentration of H2O2 is determined by the amount of Fe(CN)6 in the positive electrode electrolyte at the end of battery / stack discharge. 3- The molar concentration ratio is 1:4-2:
1.
3. The method for recovering the positive electrolyte of the alkaline iron-based liquid flow battery according to claim 2, characterized in that: The amount of H2O2 and the Fe(CN)6 in the positive electrode electrolyte at the end of battery / stack discharge 3- The molar concentration ratio is 1:
1.
4. The method for recovering the positive electrolyte of the alkaline iron-based liquid flow battery according to claim 1, characterized in that: The alkaline solution is one of NaOH solution, KOH solution and LiOH solution or a mixture of more than one of them.
5. The method for recovering the positive electrolyte of the alkaline iron-based liquid flow battery according to claim 1, characterized in that: Fe(CN)6 in the positive electrolyte 3- The concentration was measured by UV-visible spectrophotometer.
6. The method for recovering the positive electrolyte of the alkaline iron-based liquid flow battery according to claim 1, characterized in that: The green reducing agent is added after the battery / electrical stack has been running for a period of time. During the process of adding the green reducing agent, the positive electrode electrolyte may circulate through the battery / electrical stack or not.
7. The method for recovering the positive electrolyte of the alkaline iron-based liquid flow battery according to claim 1, characterized in that: The positive electrode electrolyte can be restored multiple times by adding a green reducing agent.
8. The method for recovering the positive electrolyte of the alkaline iron-based liquid flow battery according to claim 1, characterized in that: The reduction reaction time is 1 minute to 5 hours.
9. The method for recovering the positive electrolyte of the alkaline iron-based liquid flow battery according to claim 1, characterized in that: The alkaline iron-based flow battery includes an alkaline zinc-iron flow battery, an alkaline zinc-iron-nickel hybrid flow battery, an alkaline all-iron flow battery, and an alkaline quinone-iron flow battery.
Citation Information
Patent Citations
Online recovery method for positive electrolyte of zinc-iron flow battery
CN111261889A
Electrolyte for all-vanadium redox flow battery and preparation method thereof, and all-vanadium redox flow battery including the electrolyte
CN101572319A
Method for recycling vanadium electrolytic solution
CN106340657A